Palliative and End-of-life Care Competencies among Registered Nurses in Regional Health 11 - รองเมือง ดาราวรรณ; นาคฉัตรีย์ ฉันทนา; ทองเพชร เพ็ญศรี (Journal of The Royal Thai Army Nurses, 2018)
The purpose of this cross-sectional survey research was to explore the palliative and end-of-life care competencies among registered nurses in Regional Health 11. The sample consisted of 349 registered nurses, who work in the hospital under Regional Health 11. The proportional stratified random sampling was used to select the sample. The questionnaires were mailed and a total of 331 were returned. The response rate was 94.84. The research instruments composed of 1) demographic data questionnaire and 2) palliative and end-oflife care among registered nurse questionnaire. The data were analyzed using descriptive statistic and Pearson’s correlation. The results revealed that: 1) Most of the sample has knowledge on palliative and end-of-life care in moderate level (54.10 percent), attitude on death and end-of-life care in high level (82.50 percent), and practice on end-of-life care in moderate level (63.70 percent). 2) Knowledge of palliative and end-of-life care has a significant positive correlation with attitude in palliative and end-of-life care (r = .216, p <.001) and attitude in palliative and end-of-life care has a significant positive correlation with practice in palliative and end-of-life care (r = .272, p <0.001). The results from this suggested that the knowledge and practice skills in palliative and end-of-life care among registered nurses are limited. However, they have the good attitude in caring patients. Training for palliative and end-of-life care competencies development is required for nurses in order to provide quality of care to patients.